2004
DOI: 10.1002/cne.20037
|View full text |Cite
|
Sign up to set email alerts
|

Subpial and stellate cells: Two populations of interneurons in turtle visual cortex

Abstract: Turtle visual cortex has three layers and receives direct input from the dorsolateral geniculate complex of the thalamus. The outer layer 1 contains several populations of interneurons, but their physiological properties have not been characterized. This study used intracellular recording methods followed by filling with Neurobiotin to characterize the morphology and physiology of two populations of layer 1 interneurons. Subpial cells have somata positioned in the outer third of layer 1 and dendrites confined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Similarly, different populations of inhibitory interneurons in turtle DCx subserve mainly feed-forward (subpial cells; Mancilla et al 1998) or feedback (Mancilla et al 1998;Connors and Kriegstein 1986) inhibition. Axonal reconstructions of DCx interneurons (Colombe et al 2004) and immunocytochemical labeling (Reiner 1991(Reiner , 1993 suggest the existence of morphologically and physiologically identifiable classes of inhibitory interneurons. It remains to be shown that those groupings also share functional similarities with those in PCx.…”
Section: Vertical Connectivitymentioning
confidence: 99%
“…Similarly, different populations of inhibitory interneurons in turtle DCx subserve mainly feed-forward (subpial cells; Mancilla et al 1998) or feedback (Mancilla et al 1998;Connors and Kriegstein 1986) inhibition. Axonal reconstructions of DCx interneurons (Colombe et al 2004) and immunocytochemical labeling (Reiner 1991(Reiner , 1993 suggest the existence of morphologically and physiologically identifiable classes of inhibitory interneurons. It remains to be shown that those groupings also share functional similarities with those in PCx.…”
Section: Vertical Connectivitymentioning
confidence: 99%
“…After being surgically removed from the cranium and bathed in oxygenated artificial cerebrospinal fluid, an intact turtle brain (with eyes attached) can display essentially normal electrophysiological activity in response to visual stimulation (Kriegstein, 1987;Fan et al, 1993). This isolated turtle eye-brain preparation has been extensively used in electrophysiology (Kriegstein, 1987;Fan et al, 1993;Mancilla et al, 1998;Colombe et al, 2004) and optical imaging (Senseman, 1996;Prechtl et al, 1997;Senseman, 1999) in the study of visual function since 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…This is presumably because the density of geniculate synapses on lateral pyramidal cells in the rostral cortex is much higher than the density of geniculate synapses on medial or lateral pyramidal cells in the caudal cortex. Subpial cells have their somata and dendrites embedded in the fascicle of geniculate afferents that courses across the cortex (Colombe et al, 2004). Stellate cells have dendrites that extend into the band of geniculate afferents.…”
Section: Feedforward and Feedback Pathwaysmentioning
confidence: 99%